Hypermodernity, Family and Violence: A Psychosocial Analysis of Contemporary Relationships - Campos Gómez, Aline Aleida del Carmen; Romero Aguirre, Gladys de los Ángeles; Cerino Soberanes, Alba; Gómez Gallardo, Cynthia del Carmen; Peralta Jiménez, Yesenia (Emerging Trends in Education, 2026)
Hypermodernity, characterized by the acceleration of time, accelerated connectivity, and the fragility of bonds, has transformed parenthood and affective configurations. In this context, violence manifests not only explicitly but also as a normalized expression of the breakdown of bonds. From a psychosocial perspective, this study examines the crisis in the parental function and how it generates dysregulated attachment patterns and emotional difficulties in children and adolescents. To address this dynamic, parenting skills must adapt, emphasizing emotional presence, normative consistency, active listening, and emotional self-regulation in adults. For this purpose, Bandura’s Social Learning Theory is used to understand the imitation and transmission of behaviors, as well as Bronfenbrenner’s Economic Theory to situate the individual within interconnected systems. The findings show that parental dysregulation, normative inconsistency, and a lack of emotional skills increase psycho-emotional vulnerability and favor the formation of fragile bonds as well as the emergence of aggressive behaviors, which underscores the urgency of strengthening parenting and family bonds from a psychological perspective that integrates empathy, redefines bonds, and rebuilds the Self in a fragmented world.